2017
DOI: 10.1038/srep40747
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Waveforms Decrease Lethal Thresholds in High Frequency Irreversible Electroporation Therapies

Abstract: Irreversible electroporation (IRE) is a promising non-thermal treatment for inoperable tumors which uses short (50–100 μs) high voltage monopolar pulses to disrupt the membranes of cells within a well-defined volume. Challenges with IRE include complex treatment planning and the induction of intense muscle contractions. High frequency IRE (H-FIRE) uses bursts of ultrashort (0.25–5 μs) alternating polarity pulses to produce more predictable ablations and alleviate muscle contractions associated with IRE. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 55 publications
2
36
0
Order By: Relevance
“…For this reason, the delivery of bursts consisting of asymmetric bipolar pulses has been proposed and it has indeed been experimentally shown that they significantly reduce the IRE thresholds compared to bursts of regular bipolar pulses (Sano et al 2017). However, due to the charge imbalance of the asymmetric pulses, the stimulation thresholds are also likely to be significantly reduced.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, the delivery of bursts consisting of asymmetric bipolar pulses has been proposed and it has indeed been experimentally shown that they significantly reduce the IRE thresholds compared to bursts of regular bipolar pulses (Sano et al 2017). However, due to the charge imbalance of the asymmetric pulses, the stimulation thresholds are also likely to be significantly reduced.…”
Section: Resultsmentioning
confidence: 99%
“…This contingency was also tested here. Table 3 shows the modeled stimulation thresholds for a nerve termination in a homogeneous field and the IRE thresholds from (Sano et al 2017) for different waveforms. Although the IRE thresholds with asymmetric pulses are reduced about threefold compared to thresholds with symmetric pulses, the excitation thresholds are reduced in more than an order of magnitude.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Sano et al . 40 found that asymmetric high frequency IRE produced a larger ablation zone compared to symmetric high frequency IRE. On the other hand, Frandsen et al .…”
Section: Introductionmentioning
confidence: 85%
“…Sano et al . 48 reported that the delivery of ~1 μs pulses leads to the formation of numerous small pores rather than rapid cell membrane destruction caused by pore expansion. Moreover, as we calculated earlier 41 , short high-voltage also suggested that SHV (2 μs) pulses contribute less to pore development and produce small pores, which can recover easily after the pulses.…”
Section: Discussionmentioning
confidence: 99%